Mastering blockchain A deep dive into distributed ledgers, consensus protocols, smart contracts, DApps, crytocurrencies, Ethereum, and more - Bashir, Imran (Packt Publishing, 2020)
This book covers the basics, including blockchain's technical underpinnings, cryptography and consensus protocols. It also provides you with expert knowledge on decentralization, decentralized application development on Ethereum, Bitcoin, alternative coins, smart contracts, alternative blockchains, and Hyperledger.